2016
DOI: 10.3201/eid2207.160109
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Distribution of Lethal Amphibian FungusBatrachochytrium salamandrivoransin Europe

Abstract: Emerging fungal diseases can drive amphibian species to local extinction. During 2010–2016, we examined 1,921 urodeles in 3 European countries. Presence of the chytrid fungus Batrachochytrium salamandrivorans at new locations and in urodeles of different species expands the known geographic and host range of the fungus and underpins its imminent threat to biodiversity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
155
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 131 publications
(160 citation statements)
references
References 9 publications
3
155
0
2
Order By: Relevance
“…Batrachochytrium salamandrivorans (Bsal) is a recently discovered species of salamander-specific chytrid [58] that has been introduced into Europe, where it is causing mass dieoffs and population declines in several species [58,59]. Field and museum sampling has shown that Bsal has been present in Asia for over 150 years and is present in the wild in at least three countries [58 -60], although the impact on Asian populations is not known.…”
Section: (V) Salamander Chytridmentioning
confidence: 99%
See 1 more Smart Citation
“…Batrachochytrium salamandrivorans (Bsal) is a recently discovered species of salamander-specific chytrid [58] that has been introduced into Europe, where it is causing mass dieoffs and population declines in several species [58,59]. Field and museum sampling has shown that Bsal has been present in Asia for over 150 years and is present in the wild in at least three countries [58 -60], although the impact on Asian populations is not known.…”
Section: (V) Salamander Chytridmentioning
confidence: 99%
“…For example, they found that Alytes obstetricans in the Netherlands is infected but not declining, whereas populations of that species in upland areas of Spain are highly susceptible. As Bsal continues to spread in the region [59], researchers will have opportunity to establish capture-mark-recapture studies to quantify the response of native amphibians to co-infection by multiple chytrid lineages.…”
Section: (Iii) Europementioning
confidence: 99%
“…Since this fungus has been found in wild Asian newts, it is expected that Bsal is native to Asia and has recently been introduced into Europe by humans [11]. Since 2010, observed Dutch populations of fire salamanders ( Salamandra salamandra ) have drastically declined due to Bsal infections, with sometimes less than one percent survival rate (the latter studied in one population only) [12,13]. In subsequent years, Bsal infections have been recorded in additional species and nearby sites (within a radius of about 100 km from first noted outbreaks) in Belgium and Germany, and it appears that Bsal is spreading in its invasive range [13].…”
Section: Introductionmentioning
confidence: 99%
“…Since 2010, observed Dutch populations of fire salamanders ( Salamandra salamandra ) have drastically declined due to Bsal infections, with sometimes less than one percent survival rate (the latter studied in one population only) [12,13]. In subsequent years, Bsal infections have been recorded in additional species and nearby sites (within a radius of about 100 km from first noted outbreaks) in Belgium and Germany, and it appears that Bsal is spreading in its invasive range [13]. According to these authors, to date Bsal infections in Europe in the wild are known in one salamander and two newt species at 14 sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation